AN IMPROVED VOLTAGE REGULATION OF A DISTRIBUTION NETWORK USING FACTS - DEVICES (Nigerian Journal of Technology, 2013)
This paper comparatively explored the power quality of a thirteen bus, 33/11kv distribution network. The analysis of this network was actualized using the conventional load flow equation modeling. In furtherance to the mathematical modeling of the network analysis was the incorporation of a Static Compensator (STATCOM), a Flexible Alternating Current Transmission System Device which is power electronic-controlled on the specified bus under study. The Newton-Raphson Load flow equation modeling was a veritable tool applied in this analysis to determine the convergence points for the voltage magnitude, power (load) angle, power losses along the lines, sending end and receiving end power values at the various buses that make up the thirteen bus network. The graphical representations of the iteration results obtained from Newton-Raphson load flow analysis were presented to show the effects of injecting a Flexible Alternating Current Transmission System Device on the power line over the generally known conventional technique that employs electromechanical concepts.